2021
DOI: 10.3354/esr01117
|View full text |Cite
|
Sign up to set email alerts
|

Mark-recapture estimates suggest declines in abundance of common bottlenose dolphin stocks in the main Hawaiian Islands

Abstract: Species conservation relies on understanding population demographics, yet this information is lacking for many species and populations. Four stocks of common bottlenose dolphins Tursiops truncatus inhabiting the waters surrounding the main Hawaiian Islands (USA) are exposed to anthropogenic disturbances including fisheries interactions, tourism, naval activities, ocean noise, and contaminants. Although these stocks are managed under the Marine Mammal Protection Act, a demographic assessment has not been undert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Given the logistical and funding challenges of conducting cetacean research in Galaṕagos, we suggest that the development of a collaborative research agenda should include specific actions aimed at establishing and strengthening meaningful partnerships between foreign and local researchers, and include the involvement of (Palacios and Salazar, 2002;Denkinger et al, 2013;Denkinger et al, 2020), or the population assessment surveys for cetaceans conducted through a collaboration between U.S. academics and the Ecuadorian Navy through INOCAR, its institute for oceanographic and Antarctic research (Biggs et al, 2017;O'Hern et al, 2017). Continued partnership with the local tourism industry, in particular, would provide additional opportunities for participation by trained naturalists and citizen scientists in opportunistic but valuable data collection that would enhance and enrich research goals in a relatively inexpensive manner (e.g., Van Cise et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Given the logistical and funding challenges of conducting cetacean research in Galaṕagos, we suggest that the development of a collaborative research agenda should include specific actions aimed at establishing and strengthening meaningful partnerships between foreign and local researchers, and include the involvement of (Palacios and Salazar, 2002;Denkinger et al, 2013;Denkinger et al, 2020), or the population assessment surveys for cetaceans conducted through a collaboration between U.S. academics and the Ecuadorian Navy through INOCAR, its institute for oceanographic and Antarctic research (Biggs et al, 2017;O'Hern et al, 2017). Continued partnership with the local tourism industry, in particular, would provide additional opportunities for participation by trained naturalists and citizen scientists in opportunistic but valuable data collection that would enhance and enrich research goals in a relatively inexpensive manner (e.g., Van Cise et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Makako Bay is known as a traditional resting area for spinner dolphins (Tyne et al, 2018), and pantropical spotted dolphins sometimes join spinner dolphins in these resting bays. In contrast to spinner dolphins, a recent study showed that the abundance of the Hawaiʻi Island bottlenose dolphin stock appears to be relatively stable and in the low 100 s (the 2018 abundance estimate was 136 individuals, 95% CI [61, 303]; Van Cise et al, 2021). Bottlenose dolphins off Hawaiʻi Island have high levels of site fidelity and genetic differentiation from other populations in the Hawaiian Islands (Baird et al, 2009; Martien et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…We identified 36 individual bottlenose dolphins at the farm, about one-quarter of the estimated Hawaiʻi Island resident population (Van Cise et al, 2021). Twenty-two of the dolphins seen at the farm were repeatedly documented there.…”
Section: Patterns Of Farm Associationmentioning
confidence: 99%
“…Mark‐recapture is a common approach used to track individuals through time and can be used to obtain estimates of abundance. The approach considers encounter histories of marked individuals over multiple capture events and has been widely used for marine animals (e.g., Claassens & Harasti, 2020; Grossman et al, 2019; Harasti, 2016; Harasti et al, 2012; Martin‐Smith, 2011; Shine et al, 2021; Van Cise et al, 2021). Depending on the model used, assessments can be made of population parameters, such as survival and probability of re‐capture (e.g., Cormack, 1964; Jolly, 1965; Seber, 1965), probability of entry to a population (e.g., Schwarz & Arnason, 1996), recruitment, and population growth (e.g., Link & Barker, 2005; Pradel, 1996).…”
Section: Introductionmentioning
confidence: 99%